2017
DOI: 10.11648/j.sjee.20170502.12
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Optimization of Lipid Extraction from Wastewater Scum Sludge and Saponifiable Lipids Composition Analysis

Abstract: Abstract:In the present study, Design of Experiment (DoE) as a statistical method was adopted for optimizing conditions for lipid extraction from scum sludge. Four different extraction variables were investigated: methanol to hexane ratio (%), solvent to sludge ratio (ml/g), temperature (°C), and extraction time (h). During the optimization process, saponifiable lipids (SLs) content of the extracted lipid was analyzed. Screening experiments revealed that methanol to hexane ratio (X1), solvents to sludge ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
(61 reference statements)
1
0
0
Order By: Relevance
“…Since the FFA content of SS was as high as 38.5%, an alkaline catalyst was not suitable for biodiesel production. The low biodiesel conversion, even with the acid catalyst, may be due to the high level of polar lipids and unsaponifiable chemicals, such as hydrocarbon, sterols, and waxes in the extracted SS lipids [23,34,35]. A previous study reported that the amount of unsaponifiable chemicals accounted for 28% of SS lipids [35], which conformed with the value obtained in the present study (21.6%).…”
Section: Biodiesel Production Using Lipids From a Single Feedstocksupporting
confidence: 91%
“…Since the FFA content of SS was as high as 38.5%, an alkaline catalyst was not suitable for biodiesel production. The low biodiesel conversion, even with the acid catalyst, may be due to the high level of polar lipids and unsaponifiable chemicals, such as hydrocarbon, sterols, and waxes in the extracted SS lipids [23,34,35]. A previous study reported that the amount of unsaponifiable chemicals accounted for 28% of SS lipids [35], which conformed with the value obtained in the present study (21.6%).…”
Section: Biodiesel Production Using Lipids From a Single Feedstocksupporting
confidence: 91%